2017
DOI: 10.1371/journal.pone.0181967
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester fetal growth restriction and the occurrence of miscarriage in rural Bangladesh: A prospective cohort study

Abstract: Fetal growth restriction in early pregnancy increases the risk of adverse pregnancy outcome, which has a significant social and psychological impact on women. There is limited information related to community-based study to evaluate early indicators related to miscarriage. The aim of this study is to examine the relationship between fetal growth restriction, measured by ultrasound crown-rump length (CRL), and subsequent occurrence of miscarriage in pregnant women in rural Bangladesh. The study was conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This association can be explained by the various endocrine and metabolic changes, such as altered secretion and ineffective action of insulin, leptin, resistin, ghrelin, in addition to changes in the metabolism of steroids that can lead to spontaneous abortion. 5,9,11,16,21,22 In contrast, this association has not been found in other studies, 9,18,20 which noticed increased fertility in obese women. However, the chance of miscarriage in these women was also greater than in eutrophic women.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This association can be explained by the various endocrine and metabolic changes, such as altered secretion and ineffective action of insulin, leptin, resistin, ghrelin, in addition to changes in the metabolism of steroids that can lead to spontaneous abortion. 5,9,11,16,21,22 In contrast, this association has not been found in other studies, 9,18,20 which noticed increased fertility in obese women. However, the chance of miscarriage in these women was also greater than in eutrophic women.…”
Section: Discussionmentioning
confidence: 60%
“…10 A 5-year increase in maternal age increases the risk of miscarriage 1.5 times. 5,11,12,13 However, some studies have noticed a contrary association. 1,[14][15][16][17][18] One explanation for this divergence lies in the fact that the studies that associated the maternal age above 35 years of age with abortion were performed in developed countries, where women are likely to become pregnant at an older age; and studies that address maternal age below 35 as a risk factor have been carried out in developing countries, where women become pregnant earlier, increasing the likelihood of miscarriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Bangladesh also reported a vitalrelationship between negative CRL z-score categories and the probability of miscarriage. 12 The mean maternal age was also significantly higher (30.50 vs 25.74, p-value< 0.01) in the miscarried group than in the continued pregnancy group. Significant differences were found between the maternal age groups (p-value<0.01).…”
Section: Discussionmentioning
confidence: 87%
“…Yasmin et al in Bangladesh, showed that low birth weight accompanied by preterm birth resulted in 75% of the neonatal mortality, of which 84% occurred 0 to 6 days post birth [ 20 ]. Studies that have examined the rate of miscarriage in Bangladesh have identified other risk factors including lower socioeconomic status, short birth spacing between pregnancies, and mothers aged over 35 years [ 19 , 22 ]. Furthermore, many epidemiological studies on arsenic-related health effects have been conducted in the past two decades.…”
Section: Introductionmentioning
confidence: 99%